Collaborative wisdom from pervasive logic to effective operational leadership - Park, Greg. (Burlington, Vt. : Gower Pub., 2013)
Greg Park argues that corporate superstars collapse not primarily due to poor products, inadequate market penetration, financial mismanagement or self-aggrandisement, but rather by a leadership lacking the fundamental values, principles, perspectives, attributes and capabilities for long term organisational survival. The resultant inadequate cognitive mental process of leadership invites inevitable failure, through loss of confidence, motivation, cohesion, advocacy and energy amongst the community of stakeholders. Collaborative wisdom is the existence within the dominant coalition of an organi
Sounds Reasonable: But How Does it Work in the Context of My Present Role?
Description based upon print version of record.
Includes bibliographical references and index.
English
Description based on publisher supplied metadata and other sources.
Keywords: Leadership; Organizational effectiveness; Electronic books